Desain Petak Sawah Rawa Lebak Pematang untuk Pembudidayaan Padi-Ikan - Dian Septi Hastuti; Edward Saleh; Hilda Agustina (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
The research objective was to develop the design of paddy field plot in ridge lowland swamp for rice-fish cultivation. The method used in this study was descriptive in form of data collecting through direct field observation and from related institutions. The water balance and water pond dimension were mathematically calculated and the results would be compared to water balance from field observation. The observed parameters were effective rainfall, height of water table, crop water requirement, infiltration, percolation, evaporation, water pond dimension and paddy field plot size. The results showed that maximum storage volume of pond that was required to fulfill irrigation water requirement for rice plants as well as for fish cultivation was 44.2 mÂ³/month. Dimension of designed pond had length of 18.48 m, width of 2.4 m and depth of 1 m.